NUZYUZ DAN KEKERASAN DALAM RUMAH TANGGA (KDRT) DALAM PERSFEKTIF HUKUM ISLAM DAN HUKUM PIDANA - Rafianti, Fitri; Pratama Sinaga, M. Hary Angga (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2023, 2023)
This study is here to take one side that has not been discussed in recent studies by offering an argument that acts of domestic violence can be committed by husbands or wives against their respective partners, which can be categorized as nusyūż acts. This behavior can be damaging and has the potential to strongly shake the joints of domestic life with a series of impacts caused, including the worst impact is divorce. That nusyūż due to domestic violence can have a negative influence on household harmony, and can also hurt social life and child psychology, This study uses a design with a normative juridical approach. Where the approach to laws and other legal regulations is interpreted as the process of investigating or examining in depth, detail, and detail on an event or case that occurs. The juridical approach, is a legal approach carried out by studying the consistency/compatibility between the constitution and other laws, while the legal research approach is regarding the enactment or implementation of normative legal provisions in action on every particular legal event that occurs in society.